Economic Impact and Determinants of Adoption of Improved Maize Production Technologies Package in Oyo State, Nigeria - Obayelu, Abiodun Elijah; Ogunmola, Omotoso Oluseye; Ajayi, D. O. (Journal of Agricultural Sciences (Belgrade), 2018)
The problem of what production technologies to adopt, and the degree to which farm operations should be improved for attainment of optimum economic benefit have remain unsolved. This study analysed the economics and determinants of adoption of improved maize (Zea mays) production technology package in Oyo State of Nigeria. Multistage sampling procedure was employed to select one hundred and twenty maize producing farmers for the study in 2016. Data for the study were collected using structured questionnaire and analyzed with descriptive statistics and Adoption index, Regression analysis and the standard enterprise budgetary analysis. Results from the regression analysis showed that variables such as sex, farming experience, years of education, extension visits, and level of awareness of the technologies have significant and positive influence on adoption of improved maize technologies in the study area. Findings from budgetary analysis revealed that improved maize production technology adopters made N438,367.23 compared to N374,426.43 profits per hectare of maize produced during the year of survey by the non-adopters. The result further revealed that on every naira invested in maize production, the adopters were able to make N7.64k in return compared to N6.00 returns by the non-adopters. More awareness of maize production technologies through the extension agents, social network is needed inorder to increase the level of the adoption maize technology.